Invasive plant removal strategies and native plant community recovery in Ontario, Canada - Bennett, Lindsay (Université d'Ottawa / University of Ottawa, 2020)
The introduction and spread of invasive species are of major conservation concern. Invasive plant species are hypothesized to impact the population dynamics of native flora, including species at risk (SAR), and may disrupt the functioning of the plant communities which they invade. Some native plant populations may be more vulnerable due to pre-existing factors such as fragmented habitat, poor competitive nature, and/or limited geographical ranges. Because of this, the presence of one or more invasive species is frequently cited as a leading cause of at-risk species decline. However, the actual evidence for this link is weak and the mechanisms are unclear. In this study, I aimed to (1) determine the effect of invasive management schemes on the recovery of native plant communities and to (2) examine the role of factors such as method of removal and duration of invasive removal at two conservation areas in southern Ontario. After 12 candidate study areas were surveyed, two were chosen for the study (for logistical reasons). Specifically, pairs of ‘control’ and ‘invasive’ removal sites were established at St. Williams Conservation Reserve, near Turkey Point Provincial Park, ON (N = 10) and Bruce Peninsula National Park, ON (N = 8) through May - August 2018. Plots were surveyed for native and invasive plant species richness and abundance using transect methods. I found a significant difference in the abundance of native and invasive plants between control and treatment plots at St. Williams Conservation Reserve and Bruce Peninsula National Park, although the trends were in the opposite direction. Neither site had a significant difference in plant diversity between treatment types. I discuss my findings in light of the differences in land use history and management at the two areas and their implications for invasive removal schemes to manage for native plant conservation.